Guru Penggerak Sebagai Bentuk Peningkatan Kualitas Pendidikan - N Nurjannah; Ericha Tiara Hutamy; N Nirmala; Putri Nirmalasari; Ayu Lestari (Faktor : Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the role of driving teachers in improving the quality of education in Indonesia. Without the role of a teacher, education will not run well even though advanced technology has been used, because the teacher's role cannot be completely replaced by tools or technology. The research method used is a qualitative method with a literature review (library research). The results of the study reveal that education in Indonesia is currently implementing a pattern of education with teacher drivers in the independent learning curriculum. This driving teacher is an individual who can provide direction to his students to improve themselves thoroughly and have creative and innovative thinking. A driving teacher has a dual task as a leader, not only preparing a lesson plan (RPP) and explaining its contents, but a driving teacher must have the will and capacity to lead, innovate, and make improvements.